Ray - Hackford, Taylor; Benjamin, Stuart; Baldwin, Howard; Baldwin, Karen (Universal City, California Universal Studios, 2005)
Jamie Foxx (Collateral) stars as the one-of-a-kinf innovator of soul who overcame impossible odds to become a music legend. Ray is the triumphant and remarkable story of one of America's true musical genuises, Ray Charles. From his humble beginnings in the South through his meteoric rise to the top of American music charts, Ray's inspirational journey is a tale of hope, redemption and the power of the human spirit. "Ray is Electrifying" hails Peter Travers of Rolling Stone. Witness the incredible true story of a musician who fought harder and went further than anyone could imagine.
Executive producers, William J. Immerman, Jaime Rocker King ; Screenplay by James L. White.
Jamie Foxx, Kerry Washington, Regina King.
Dolby digital.
In English with Español and Francais.
Keywords: Charles, Ray, 1930-2004 -- Drama; Singers -- United States -- Drama; Feature films